A Decade of Science, Innovation and Transformation: CCAFS Impact In East Africa - Sally, Hilmy; Mungai, Catherine; Makonnen, Brook T. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This legacy document is intended to capture the key outcomes and highlight the impact of the CCAFS East Africa regional program over the past decade. The reporting is structured around the Strategic Research Pillars detailed in the CCAFS-EA Strategy 2019–2021, apart from the fact that aspects related to Gender, Youth and Socially Inclusive Growth (Pillar 4) are not treated separately but integrated into the other three pillars.The report also highlights the influence and likely contributions of CCAFS East Africa to upcoming endeavors such as OneCGIAR, Accelerating the Impact of CGIAR Climate Research for Africa (AICCRA), and the Two Degree Initiative for Food and Agriculture (2DI).